Visible Women in Chinese Feminist Movies. Issue 1 (10th March 2022) - Tang, Qing
Abstract: The past decades have witnessed the birth and growth of feminist movies in China since the Second Enlightenment following China's reform and opening up. While a movie, like other forms of art, mirrors its times and cultural milieu, the female characters reflect specific groups of women living in specific contexts. Focusing on the works of three representative female directors born in the 1930s, 1950s, and 1970s, this article illustrates the development of China's feminist movies by analyzing the themes they highlight and decoding the underlying similarities of their female characters as they are shaped by Chinese culture.